(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Developing adaptive educational models has become a strategic priority in modern special education, particularly for learners with visual impairments who require individualized pedagogical and psychological support throughout the educational-corrective process. This study aims to develop and validate an adaptive model of pedagogical and psychological support designed to improve the effectiveness of educational-corrective practices in specialized educational institutions. The research employed a mixed-methods design integrating theoretical analysis, pedagogical modeling, classroom observation, interviews, questionnaires, diagnostic assessment, and a pedagogical experiment involving 151 primary-level learners with visual impairments from specialized educational institutions in Uzbekistan. The proposed adaptive model consists of five interconnected components: comprehensive diagnostic assessment, individualized educational planning, adaptive pedagogical intervention, continuous psychological support, and developmental monitoring with feedback mechanisms. The effectiveness of the model was evaluated by analyzing changes in learners’ academic engagement, communication competence, social adaptation, and learning motivation during the experimental implementation. The findings indicate that the adaptive model provides a systematic framework for coordinating educational and psychological support according to individual developmental characteristics. The integration of diagnostic data with individualized instructional strategies enhanced learners’ educational participation and facilitated more effective corrective interventions. Furthermore, continuous monitoring enabled timely modification of educational trajectories in response to learners’ developmental progress.